Adipogenic Gene Expression in Gilthead Sea Bream Mesenchymal Stem Cells from Different Origin - Salmerón, Cristina; Riera-Heredia, Natàlia; Gutiérrez, Joaquim; Navarro, Isabel; Capilla, Encarnación (Frontiers in Endocrinology, 2016)
During the last decades, adipogenesis has become an emerging field of study in aquaculture due to the relevance of the adipose tissue in many physiological processes and its connection with the endocrine system. In this sense, recent studies have translated into the establishment of preadipocyte culture models from several fish species, lacking sometimes information on the mRNA levels of adipogenic genes. Thus, the aim of this study was to determine the gene expression profile of gilthead sea bream (Sparus aurata) primary cultured mesenchymal stem cells (MSCs) from different origin (adipose tissue and vertebra bone) during adipogenesis. Both cell types differentiated into adipocyte-like cells accumulating lipids inside their cytoplasm. Adipocyte differentiation of MSCs from adipose tissue resulted in down-regulation of several adipocyte-related genes (such as lpl, hsl, pparα, pparγ and gapdh2) at day 4, gapdh1 at day 8, and fas and pparβ at day 12. In contrast, differences in lxrα mRNA expression were not observed, while g6pdh levels increased during adipocyte maturation. Gapdh and Pparγ protein levels were also detected in preadipocyte cultures; however, only the former increased its expression during adipogenesis. Moreover, differentiation of bone-derived cells into adipocytes also resulted in the down-regulation of several adipocyte gene markers such as fas and g6pdh at day 10 and hsl, pparβ and lxrα at day 15. On the other hand, the osteogenic genes fib1a, mgp and op remained stable, but an increase in runx2 expression at day 20 was observed. In summary, the present study demonstrates that gilthead sea bream MSCs from both adipose tissue and bone differentiate into adipocyte-like cells, although revealed some kind of species- and cell lineage-specific regulation with regards to gene expression. Present data also provide novel insights into some of the potential key genes controlling adipogenesis in gilthead sea bream that can help to better understand the regulation of lipid storage in fish.